Nematopsis Schneider, 1892 in Nerite Gastropods From Saint Kitts, With a Phylogenetic Study of the Genus, and Placement Within the Phylum Apicomplexa Levine, 1970 - Herbert, Nicole A. M. (2025)
The Apicomplexa are obligate unicellular parasites found in terrestrial and aquatic environments. Nematopsis are found infect-ing marine invertebrates in a life cycle involving mollusks and crustaceans. In the present study, mantle and muscle tissues fromnerite gastropods were microscopically examined for Nematopsis using wet mounts and histology. Oocysts contained one singlesporozoite surrounded by an ellipsoidal wall and were surrounded by a parasitophorous vacuole within a host phagocyte. Lengthand width of fresh oocysts were measured and compared between host species. DNA was extracted from infected tissue, andregions of the rRNA gene were amplified using novel primers. Nematopsis-infected tissues from scallops from Argentina andScotland were used as controls. The sizes of oocysts observed in nerite hosts from Saint Kitts were not significantly different.DNA sequences of Nematopsis isolated from nerite hosts in this study were identical and phylogenetically related to sequencesobtained from scallops. Bayesian and maximum likelihood phylogenetic analyses robustly place the Nematopsis DNA sequencesfrom this study with Nematopsis from scallops in Florida and members of the family Porosporidae. We conclude that marineNematopsis will group within this clade or within the Porosporidae. We have provided specific oligonucleotide primers to assistwith the molecular study of the Porosporidae.